STUDY OF L-TRYPTOPHAN IN AN EXPERIMENTAL MODEL OF DEPRESSION CAUSED BY ALZHEIMER’S DISEASE - Andressa Leticia Miri; Andressa Panegalli Hosni; Jossinelma Camargo Gomes; Ivo Ilvan Kerppers; Mário César da Silva Pereira (Journal of Physical Education)
ABSTRACT Alzheimer’s is a neurodegenerative disease characterized by cognitive impairment commonly associated with mood disorders, which trigger depressive reactions and compromise mental performance and functionality. The objective of the present study was to verify the effects of L-tryptophan and to analyze motor behavior in an experimental model of depression caused by the Alzheimer’s disease process. The sample consisted of 40 Wistar rats divided equally into two groups, 20 animals treated with L-tryptophan and 20 control animals. Both groups received spatial memory training in the water maze task and were submitted to stereotaxic surgery to induce dementia. The treated group achieved better spatial memory activity than the control group in the Morris water maze. Treatment with L-tryptophan had beneficial effects on reactive memory.